83 Closed Loop Audit Examining Documentation of Advanced Trauma and Life Support (ATLS) Secondary Survey in Polytrauma Cases at The Royal Infirmary of Edinburgh (RIE). (4th May 2021) - Balfour, J; Powell-Bowns, M; Leow, J; Arthur, C
Abstract: Introduction: Secondary survey is a key aspect of the ATLS guidelines in avoiding missed injuries in polytrauma patients. Aim: Evaluate the documentation of secondary survey in polytrauma cases admitted to the RIE A+E department. Method: Standard audit protocol, retrospective data collection. Polytrauma patients and patients requiring Trauma CT were identified from the local trauma database. Primary outcome was successful completion and documentation of secondary survey. Cycle 1: All patients from 01/01/2015-01/09/2015. Local policy change included an A+E trauma booklet and policy of secondary survey on admission to Intensive Care. Cycle 2 was completed post-intervention for patients presenting between 11/01/2019-29/05/2019. Results: Cycle 1 (N = 20, N Secondary survey documented=10, mean=50%). Mean time to secondary survey was 8 hours (range 3-49). Cycle 2 (N = 28, N Secondary survey documented=24, mean=87.5%). Mean time to a secondary survey was 4 hours 30 minutes (range=1-21hrs). Significant improvement in documentation (Fisher's Exact Test, P = 0.017). Conclusions: Implementation of the secondary survey protocol and trauma booklet significantly improved documentation of secondary survey in the polytrauma patient. Evidence also suggests improved time to secondary survey. However, documentation of secondary survey is not universal indicating further improvement is required in trauma care, as the RIE moves towards becoming a National Major Trauma Centre.